Being a “colono” and being “daitsch” in Rio Grande do Sul: Language choice and linguistic heterogeneity as a resource for social categorisation - Auer, Peter; Arnhold, Jacinta; Bueno-Aniola, Cintia (Calidoscópio, 2021)
This paper investigates sociolinguistic styles as indexes to social identities in the context of the ‘German’ colonial zone in Rio Grande do Sul, Brazil. On the basis of a detailed sequential and stylistic analysis of three interactional episodes in a sindicato office it is shown that the deployment of sociolinguistic style is relevant for the display and ascription of identity-related features of ethnic belonging (daitsch) and positioning on the rural-urban continuum (colono). In particular, the paper focuses on language choice and code-switching/mixing. Key words: identity, bilingualism, German in RS.